Implementasi Kurikulum Cambridge di Al-irsyad Satya Islamic School Bandung - Vera Siti Magfiroh; Siti Qamariah; Salsabila Salsabila; N. Desti Ramadani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Islamic education in the era of globalization faces the challenge of remaining relevant to the times without losing its Islamic identity. Al-Irsyad Satya Islamic School, as one of the leading educational institutions, implements the Cambridge curriculum integrated with Islamic values to provide quality education that is internationally oriented. This study aims to analyze the implementation of the Cambridge curriculum at the preschool level at Al-Irsyad Satya, focusing on the implementation strategy, the challenges faced, and the impact on learning development.This study uses a descriptive qualitative method with a phenomenological approach. Data were collected through semi-structured interviews with teachers and principals, as well as direct observation of the learning process in preschool classes. Data analysis was conducted through data reduction techniques, data presentation, and conclusion drawing based on qualitative analysis steps. The results showed that the implementation of the Cambridge curriculum at Al-Irsyad Satya is done through the integration of Cambridge-based academic materials with Islamic values, such as noble morals and Islamic manners, which are taught in every learning activity. Challenges faced include adjusting the international curriculum to local needs and training teachers to ensure a deep understanding of both aspects. Nevertheless, the impact is very positive, especially in developing students' academic abilities, Islamic character and social skills as a whole. This study concludes that the integrative approach implemented by Al-Irsyad Satya Islamic School can serve as a model for other Islamic education institutions in adopting the international curriculum without losing Islamic values.